Myoelectric Elbow-Wrist-Hand Orthosis for an Adolescent with Hemiparesis: A Case Report. Issue 2 (9th April 2022) - Constantino, Christopher; May, Elizabeth; Flanagan, Ann; Altiok, Haluk; Harris, Gerald
ABSTRACT: Introduction: Robot-assisted therapy is an innovative approach to upper-limb rehabilitation that uses intensive, repetitive, interactive, and individualized practice as an optimal strategy to enhance motor learning. An example of upper-limb robot-assisted therapy is the myoelectric orthosis MyoPro (Myomo Inc, Cambridge, USA). It is a custom-fabricated myoelectric elbow-wrist-hand orthosis (MEWHO) with built-in surface sensors that detect the user's electromyographic (EMG) signals during muscle contraction. Studies on the MEWHO have focused mostly on elderly chronic stroke patients. None have discussed its use on the adolescent population and the considerations they face in wearing the orthosis. Case Presentation: A 15-year-old male 10th grade student with a diagnosis of right spastic hemiplegia secondary to cerebral palsy was prescribed a MEWHO because of muscle weakness of his right upper extremity, decreased functional status, and fine motor skills deficits. Results: After two occupational therapy cycles, the patient demonstrated improvements in functional strength and performance of physical activities. Despite these improvements, the patient only used the MEWHO during therapy and was less engaged with its use at home and school. Discussion: This case report presents insights on why the patient was not as proficient and interested in using the orthosis at home and school. Recommendations to address these issues include peer modeling, community outings, early intervention, and the use of family-centered approaches. Future studies are also suggested to further understand MEWHO use and the considerations for successful orthotic management in this group of patients.